Association of lipoprotein (a) and in-hospital outcomes in patients with acute coronary syndrome undergoing percutaneous coronary intervention. Issue 2 (17th February 2021) - Wu, Baoquan; Zhao, Hanjun; Liu, Changhua; Lu, Hao; Liu, Ruishuang; Long, Juan; Zhang, Zhiling; Zeng, Fanfang
ABSTRACT: Objective : The current study was to evaluate the association of Lipoprotein (a) [Lp(a)] and in-hospital outcomes in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). Methods : ACS patients undergoing PCI were retrospectively enrolled. Based on Lp(a) level, patients were divided into low (<30 mg/dL) and high (≥30 mg/dL) Lp(a) groups. Results : Compared to those with low Lp(a), patients with high Lp(a) had larger numbers of coronary arteries ≥70% stenosis and had longer coronary artery lesion (P < 0.05). After adjustment for covariates, high Lp(a) remained associated with higher odds of having coronary artery ≥70% stenosis, type C coronary lesion and pre-PCI TIMI flow grade 1/0. Patients with high Lp(a) had a higher unadjusted odds of acute stent thrombosis (odds ratio [OR] 1.10 and 95% confidence interval [CI] 1.01–2.27), congestive heart failure (OR 1.24 and 95% CI 1.15–2.38) and composite in-hospital outcomes (OR 1.28 and 95% CI 1.18–2.42). After adjustment for covariates, patients with high Lp(a) still had a higher odds of congestive heart failure (OR 1.08 and 95% CI 1.01–1.78) and composite in-hospital outcomes (OR 1.12 and 95% CI 1.04–1.81). Conclusion : In ACS patients undergoing PCI, compared to those with low Lp(a), patients with high Lp(a) had more severe coronary artery lesion, higher risk of congestive heart failure and composite in-hospital outcomes.